Discovery of 3-Arylquinoxaline Derivatives as Potential Anti-Dengue Virus Agents - Chih-Hua Tseng (International Journal of Molecular Sciences, 2019)
We designed and synthesized a series of novel 3-arylquinoxaline derivatives and evaluated their biological activities as potential dengue virus (DENV) replication inhibitors. Among them, [3-(4-methoxyphenyl)quinoxalin-2-yl](phenyl)methanol (19a), [6,7-dichloro-3-(4-methoxyphenyl)quinoxalin-2-yl](phenyl)methanol (20a), and (4-methoxyphenyl)(3-phenylquinoxalin-2-yl)methanone (21b) were found to significantly inhibit the DENV RNA expression in Huh-7-DV-Fluc cells with a potency better than that of ribavirin. Compound 19a reduced DENV replication in both viral protein and messenger RNA (mRNA) levels in a dose-dependent manner and exhibited no significant cell cytotoxicity. Notably, compound 19a exhibited a half maximal effective concentration (EC50) value at 1.29 ± 0.74 μM. We further observed that the inhibitory effect of 19a on DENV replication was due to suppression of DENV-induced cyclooxygenase-2 (COX-2) expression. Docking studies also showed that 19a caused hydrophobic interactions at the active sites with Arg29, Glu31, Tyr116, Leu138, Pro139, Lys454, Arg455, and Gln529. The calculated lowest binding energy between the 19a and COX-2 was −9.10 kcal/mol. In conclusion, compound 19a might be a potential lead compound for developing an anti-DENV agent.